A Tale of Two (Stuffed) Fish: Coastal Encounters in the Scientific Writings of Sir John Richardson - Donaldson, Christopher; Maclaine, James (Romanticism on the Net)

(untitled) (Université de Montréal, 2022)
This essay delves into the history of two stuffed fish in London’s Natural History Museum. These fish came from opposite ends of the earth: one from southern Australia, the other from northern Canada. But they were both documented and named by a Scotsman, Sir John Richardson (1787–1865). Richardson’s encounters with these fish shed light on different aspects of his career as a naval surgeon, polar explorer, and natural historian. More importantly, though, these encounters also reveal how European knowledge of the world’s coastal environments was created during the Romantic era. In considering the context and consequences of these encounters, this essay reflects on how the subject of this special issue, though nationally defined, connects with broader histories of nineteenth-century exploration and empire. The places where these fish were caught lay well beyond Scotland. Nonetheless, these fish are relevant to the study of Scotland’s coastal Romanticisms, and tracing their history invites us to rethink the geographical assumptions that often govern the study of national pasts.